2014
DOI: 10.3389/fpls.2014.00095
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular implications of plant polyamine metabolism during biotic interactions

Abstract: During ontogeny, plants interact with a wide variety of microorganisms. The association with mutualistic microbes results in benefits for the plant. By contrast, pathogens may cause a remarkable impairment of plant growth and development. Both types of plant–microbe interactions provoke notable changes in the polyamine (PA) metabolism of the host and/or the microbe, being each interaction a complex and dynamic process. It has been well documented that the levels of free and conjugated PAs undergo profound chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 163 publications
(201 reference statements)
6
115
0
1
Order By: Relevance
“…S10). ADCs and ODCs are rate‐determining steps in plant polyamine biosynthesis, and higher ADC and ODC transcription is correlated with increased plant putrescine production (Jiménez‐Bremont et al ., ). We measured expression of tomato polyamine biosynthesis genes in roots and stems following inoculation of unwounded roots.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…S10). ADCs and ODCs are rate‐determining steps in plant polyamine biosynthesis, and higher ADC and ODC transcription is correlated with increased plant putrescine production (Jiménez‐Bremont et al ., ). We measured expression of tomato polyamine biosynthesis genes in roots and stems following inoculation of unwounded roots.…”
Section: Resultsmentioning
confidence: 97%
“…Polyamines sometimes benefit pathogens and sometimes boost plant immunity (Jiménez‐Bremont et al ., ). It has been observed that ‘In plant–pathogen interactions, the organism that takes control of polyamine metabolism has the advantage’ (Jiménez‐Bremont et al ., ). Although the specific roles of polyamines in plant–microbe interactions are uncertain, there are hints.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…PAs, including putrescine, spermidine, and spermine are positively charged secondary metabolites that are associated with plant resistance to microbial pathogens (Walters 2003;Jimenez-Bremont et al 2014). BiFC and Co-IP analyses of Agrobacterium-mediated transient expression in N. benthamiana leaves verified the physical interaction of AvrBsT with CaADC1 in planta (Kim et al 2013b).…”
Section: Pepper Arginine Decarboxylase1 (Caadc1)mentioning
confidence: 99%
“…In this review, I briefly summarize current knowledge of the role of PAs in disease resistance. More comprehensive reviews of PAs in biotic stress responses, including pathogenic and beneficial interactions, are available elsewhere (Jiménez-Bremont et al, 2014).…”
Section: Introductionmentioning
confidence: 99%